Telecommunications and convergence technologies - applications and opportunities. - Chan, Chee Wei. (2011)
We would like to express our sincere gratitude to our project supervisor, Dr Alfred Seaman, for his guidance and support in this report. Our appreciation also goes to A/P John Webster and his wife for organising a very memorable and rewarding trip to Europe. The trip has provided us with an invaluable opportunity to meet and discuss EU-ASEAN relations with EC representatives, CEOs and people from the academic community. This interaction has left us with a deeper insight to the western culture which no written material can convey. We would also like to thank A/P John Williams and the staff of the School of Accountancy and Business MBA office who provided efficient administrative support for the trip to Europe and for the whole program.